Knowledge, attitude, and practices of swiftlet ranchers in sustainable swiftlet ranching in Johor, Malaysia - K. N. Vaiappuri, Selvakkumar (2013)
The swiftlet ranching is an activity that conducted in bird house that imitate cave-like environment in order to provide alternative nesting sites to lure the swiftlet birds with remain natural living style (behaviour). The swiftlet ranching activities mainly rely on the nature and environment. Thus, the environment factor is the main concern in the swiftlet industry as to keep the industry for a long term. Uncontrolled development of swiftlet houses can cause a sustainable risk to the industry. One of the main issues is regarding environmental disturbance for public surrounding the bird house. Swiftlet ranchers commonly use „bird calling sound‟ to attract the birds and build their nests in the bird house. The ranchers will keep on playing the sounds from morning until evening to attract more birds to come to their bird house The specific objectives of this study are to investigate the knowledge, attitude and practices (KAP) levels of swiftlet ranchers towards sustainable swiftlet ranching; to determine the relationship between knowledge, attitude, and practices levels of swiftlet ranchers; to examine the relationship between knowledge, attitude and practices levels and swiftlet ranchers socio-demographic profiles; determine factors that influence sustainable swiftlet ranching which affect the ranchers‟ knowledge, attitude, and practices levels of swiftlet ranchers towards sustainable swiftlet ranching and to determine the effectiveness of EBN production and socio-demographic profiles on swiftlet ranchers‟ KAP levels. A total of 136 ranchers were selected from Johor and face-to-face interviews were conducted to collect data using a structured questionnaire. The result showed that 71.3% ranchers have an adequate knowledge level. The knowledge level was determined based on overall score. Among the ranchers, 66.7% ranchers showed they have a favourable attitude towards sustainable swiftlet ranching. The result also indicated that 61.76% ranchers had high level of sustainable practices in their ranching activities. The Pearson correlation result showed that the knowledge level and attitude were positively related with scores of 0.768 and 0.827 for knowledge level and sustainable practices respectively. The relationship between attitude and practices was positively related with score of 0.932. The Pearson correlation was significant at 1% level of significance. Meanwhile, based on the results from factor analysis, three main factors were revealed to influence sustainable swiftlet ranching namely economic, social, and environment. Multiple liner regression using factor scores from the factor analysis was employed to indentify the most influential factor for sustainable practices among the respondents. The result revealed the respondents‟ practices level and economy, social and environment factors have positive relationships. Further, logistic regression was employed in this study to measure the effect of EBN production and socio-demographic factors on respondents‟ KAP levels. The study found that the socio-demographic variables such as age, level of education, attend course, EBN production, and years of experience have significant relationship between swiftlet respondents‟ KAP levels. An improvement in the government policy is urgently required. Since the results of this study clearly showed that education and attending seminars on swiftlet ranching revealed to have significant effects on respondent‟s KAP levels, more related programmes, seminars and workshops should be conducted by government agencies. The existing policy which is mainly focused on EBN production includes less focus or attention to sustainable issues in the swiftlet ranching. Sustainable practices are a grass root to ensure the survival of swiftlet industry for long term. The extensions agencies must keep working with respondents and others parties in order to improve and strengthen the swiftlet industry in Malaysia.